2019
DOI: 10.3750/aiep/02623
|View full text |Cite
|
Sign up to set email alerts
|

Stock assessment of Prochilodus nigricans (Actinopterygii: Characiformes: Prochilodontidae) using two distinct algorithms, in the context of a small-scale Amazonian fishery

Abstract: assessment of Prochilodus nigricans (Actinopterygii: Characiformes: Prochilodontidae) using two distinct algorithms, in the context of a small-scale Amazonian fishery. Acta Ichthyol. Piscat. 49 (4): 373-380. Background. Despite the importance of inland fishery, assessments of exploited inland stocks have relied on datadeficient databases, mainly in developing countries. In this paper, we employed two distinct analytical methods to evaluate the stock status of Prochilodus nigricans Spix et Agassiz, 1829, the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Recently, in the Amazon, declining stocks of some commercially important species, such as tambaqui ( Colossoma macropomum ) and curimatã ( Prochilodus nigricans ), has been identified using traditional stock assessment methods that analyze each stock individually (Campos et al., 2015; Catarino et al., 2019). In this study, we did not find a decline in mean trophic level, possibly due to high diversity of fish in the Amazon region (Dagosta & de Pinna, 2019; Oberdorff et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, in the Amazon, declining stocks of some commercially important species, such as tambaqui ( Colossoma macropomum ) and curimatã ( Prochilodus nigricans ), has been identified using traditional stock assessment methods that analyze each stock individually (Campos et al., 2015; Catarino et al., 2019). In this study, we did not find a decline in mean trophic level, possibly due to high diversity of fish in the Amazon region (Dagosta & de Pinna, 2019; Oberdorff et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Since the 1960s, with the introduction of technological innovations in fishing, some commercially important fish stocks, such as the pirarucu ( Arapaima gigas ), tambaqui ( Colossoma macropomum ), curimatã ( Prochilodus nigricans ), jaraqui ( Semaprochilodus spp. ), piramutaba ( Brachyplatystoma vaillantii ), and dourada ( Brachyplatystoma rousseauxii ) are showing signs of overfishing (Campos et al., 2015; Castello & Stewart, 2010; Catarino et al., 2019; Prestes et al., 2022). In addition to spatial and temporal constraints of stock assessment studies of these traditional fishery, all have focused on individual species, so the effects of intense fishing pressure on mixed‐species are unknown (Goulding et al., 2019; Pereira et al., 2023).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, T. angulatus is an important seed disperser (Weiss et al, 2016) whose reduction in body size can lead to a reduction of seed dispersal function, once small individuals are usually less capable of dispersing seeds and can destroy seeds by mastication (Correa et al, 2015). Effects of fishing and droughts on fish size are very poorly known in the Amazon, Fabré et al (2017) found that in drought years the fishing landed is composed mainly by small fish, and Catarino et al (2019) reported overfishing growth effect by a highly fished species ( Prochilodus nigricans ); however, no other study considered demographic and life‐history changes.…”
Section: Discussionmentioning
confidence: 99%